A Treatment-Response Comparison Study of Resting-State Functional Magnetic Resonance Imaging Between Standard Treatment of SSRI and Standard Treatment of SSRI Plus Non-dominant Hand-Writing Task in Patients With Major Depressive Disorder - Boyraz, Rabia Kevser; Kirpinar, Ismet; Yilmaz, Onur; Özyurt, Onur; Kiliçarslan, Tezer; Aralasmak, Ayse (Frontiers in Psychiatry, 2021)
Background: Researches have recently shifted from functional/structural imaging studies to Functional Connectivity (FC) studies in Major Depressive Disorder (MDD). We aimed to compare the treatment response of two groups in terms of FC changes. Methods: A total of 26 patients with right-handed women with similar sociodemographic characteristics were enrolled. Their pre-treatment resting-state functional magnetic resonance imaging (rs-f MRI) and neuropsychiatric tests were recorded and then patients were divided into two groups randomly. Standard treatment (ST) (Sertralin 50 mg /day) was given to both groups. One randomly selected group was given the “Nondominant Hand-writing Exercise (NHE)” in addition to the ST. After eight weeks of treatment, all patients were reevaluated with rs-f MRI and neuropsychiatric tests. Pre- and post-treatment FC changes within the groups and post-treatment connectivity changes between groups were evaluated. Results: Post-treatment neuropsychiatric tests were significantly different in both groups. Post-treatment ‘two brain regions’ connectivity changed in the ST group, whereas ‘ten brain regions’ connectivity changed significantly in the “ST+NHE” group. When treatment groups compared with each other after the treatment, the FC of ‘thirteen regions’ changed in the ST+NHE group. The density of the frontal and limbic regions connectivity changes in the ST+NHE draws attention and seems to be compatible with the neuropsychiatric test changes. Conclusion: NHE, which we developed with inspiration from the “Eye Movement Desensitization and Reprocessing” method caused significant differences in MDD treatment. In addition to offering a new additional treatment method, our study will also contribute to the current literature with our efforts to evaluate all brain regions and networks that may be related to MDD together, without being limited to a few regions.